Semiotic Analysis of Jana Gana Mana (2022) - R, Shylesh (Journal of Advanced Research in Journalism & Mass Communication, 2023)
The movies that provide a sense of realism to the audience are those which are having great effects on the audience. In such a case, the filmmaker can’t completely depend on dialogue. The results of the analysis show that the mise-en-scène plays an important role in an immersive experience for the audience, thus creating a sense of reality. In this research paper mise-en-scène plays the major role.This research paper uses a descriptive qualitative method of analysis. The movie’s mise-en-scène is analysed for the presence of signifiers that contribute to the narration of the film. This study semiotically analysis the movie Jana GanaMana (2022) by understanding the role of mise-en-scène in effective narration. How to cite this article: Shylesh R. Semiotic Analysis of Jana Gana Mana (2022). J Adv Res Jrnl Mass Comm 2022; 9(4): 10-14. DOI: https://doi.org/10.24321/2395.3810.202209